DFT Study of the Coordination of N-monochlorosubstituted Derivatives of the N-deprotonated Tautomer of the Biguanide - AÏDOTE, François; KUEVI, URBAIN AMAH; KPOTIN, ASSONGBA GASTON; ATOHOUN, Sylvain Guy Yacolé (My University, 2020)
Biguanides [HN=C(NR1R 2 )-NH-C(NR3R 4 )=NH] constitute an important family of molecules used as drugs in the treatment of diabetes. When R1 =R2 =R3 =R4 =H the molecule is named simply “biguanide”. The five nitrogen atoms are potential coordination sites. Several experimental works published in literature show that in complex state, therapeutic properties of the active molecules increase considerably. In fact, the chlorine atom, a preferred substitute in pharmacy, improves the effectiveness of these drugs by increasing their activities and also by reducing their side effects. Recent experiments with Zinc complexes on diabetic animals have been very successful. In the present work a theoretical study of the coordination of N-chlorine derivatives of Ndeprotonated tautomer of biguanide has been carried out. The aim is to determine, among the five nitrogen and chlorine atoms, the site most favorable to the coordination of these ligands. This determination is based on some coordination indicators. The calculations were performed by the DFT / B3LYP method in the 6-31G (d, p) orbital basis set with the Gaussian 09 and Gaussian 03 software. The DCENT-QSAR program was also used. The results of the various calculations revealed the imine nitrogen atoms as the most favorable coordination sites in the studied N-chlorosubstituted derivatives of N-deprotonated tautomeric biguanide. Complexes of these ligands with Zn (II) were modelled. The chlorine atom proved unfavorable to coordination.
Keywords: Coordination; N-chlorine derivatives; N-deprotonated; tautomer of biguanide; diabetes; DFT / B3LYP; 6-31G (d; p) orbital basis set.